A two step method for the numerical integration of stiff differential equations - Bulut, H; İnç, Mustafa (Gordon Breach Sci Publ Ltd, 2000)
We examine a single-step implicit-integration algorithm which is obtained by a modification of the well-known Simpson rule. The accuracy and stability properties of these methods are investigated. The obtained new method is a fourth-order numerical process and preserves the property of A-stability of the Simpson rule. Numerical results for the solution of certain stiff equations.
Keywords: one-step methods; stiff differential equations; A-stability; Simpson rule